Practical Web 2.0 Applications with PHP - Zervaas, Quentin (Apress : Imprint: Apress, 2008)
Want to assert yourself as a cutting-edge PHP web developer? Take a practical approach, learning by example from author Quentin Zervaas, and discover how to bring together the many technologies needed to create a successful, modern web application. In Practical Web 2.0 Applications with PHP, PHP, MySQL, CSS, XHTML, and JavaScript/Ajax development techniques are brought together to show you how to create the hottest PHP web applications, from planning and design up to final implementation, without going over unnecessary basics that will hold you back. This book includes must-have application features such as search functionality, maps, blogs, dynamic image galleries, and personalized user areas. The Zend Framework is used extensively to build the application, allowing you to focus on developing the application rather than on reinventing the wheel. Topics covered include application planning and design, setting up the application framework, using CSS for easier styling, adding dynamic effects the easy way using JavaScript libraries such as Prototype and script.aculo.us, and implementing several must-have web application features such as user login, blogs, dynamic image galleries, search functionality, mapping with Google Maps, and much more. Zervaas covers everything in a practical, tutorial style so you can start working on your own projects as quickly as possible. Create cutting-edge PHP/MySQL web applications Implement must-have functionality such as blogs, maps, search functionality, and dynamic image galleries Master styling with CSS and dynamic effects using Ajax/JavaScript libraries.